MANUSCRIPT OF HASAN MUNAWI’S MUSHAF AL-QUR’AN: STUDY OF CODICOLOGY, RASM, AND QIRA’AT - Muh Rifqi Hidayat; Nur Aini; Khoirul Imam (Program Pascasarjana UIN Sumatera Utara, 2026)
Studying manuscripts from the past is considered necessary because they contain information about history, culture, and civilization in society. This study focuses on the study review of the Qur'an manuscript Hasan Munawi (MAHM) using a codicology and philology or textology approach focusing on the discussion of rasm and qira'at. The researchers used a qualitative research method with a type of library research, while in data analysis, the researchers used the Miles and Huberman interactive model analysis. The study results show that the codicology study can be seen on the authentic cover of the manuscript, there is a Manggala as historical information, the physical condition of the manuscript is not intact, the base of the manuscript is European paper with Pro Patria and Concordia watermarks and Honig, G - & Zoon countermarks, thick and thin lines, has a manuscript size of 32.5 cm x 20.5 cm, geometric illumination and floral motifs, Arabic script, most of the writing is in the khaṭ tsuluts type with black and red ink colours. The study from a textological perspective can be seen in the inconsistent use of rasm and the qira'at using the qira'at of Imam 'Āsim in the history of Ḥafs.